Calculus: Early Transcendentals, 9th Edition - James Stewart; Daniel K. Clegg; Saleem Watson (Cengage Learning, 2020)
James Stewart's Calculus series is the top-seller in the world because of its problem-solving focus, mathematical precision and accuracy, and outstanding examples and problem sets. Selected and mentored by Stewart, Daniel Clegg and Saleem Watson continue his legacy of providing students with the strongest foundation for a STEM future. Their careful refinements retain Stewart's clarity of exposition and make the 9th Edition even more useful as a teaching tool for instructors and as a learning tool for students. Showing that Calculus is both practical and beautiful, the Stewart approach enhances understanding and builds confidence for millions of students worldwide. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.